Outcome of HIV-exposed uninfected children undergoing surgery - van Bogerijen Guido; van der Graaf Nelleke; Millar Alastair JW; Karpelowsky Jonathan S; Zar Heather J (BMC, 2011)
Abstract Background HIV-exposed uninfected (HIVe) children are a rapidly growing population that may be at an increased risk of illness compared to HIV-unexposed children (HIVn). The aim of this study was to investigate the morbidity and mortality of HIVe compared to both HIVn and HIV-infected (HIVi) children after a general surgical procedure. Methods A prospective study of children less than 60 months of age undergoing general surgery at a paediatric referral hospital from July 2004 to July 2008 inclusive. Children underwent age-definitive HIV testing and were followed up post operatively for the development of complications, length of stay and mortality. Results Three hundred and eighty children were enrolled; 4 died and 11 were lost to follow up prior to HIV testing, thus 365 children were included. Of these, 38(10.4%) were HIVe, 245(67.1%) were HIVn and 82(22.5%) were HIVi children. The overall mortality was low, with 2(5.2%) deaths in the HIVe group, 0 in the HIVn group and 6(7.3%) in the HIVi group (p = 0.0003). HIVe had a longer stay than HIVn children (3 (2-7) vs. 2 (1-4) days p = 0.02). There was no significant difference in length of stay between the HIVe and HIVi groups. HIVe children had a higher rate of complications compared to HIVn children, (9 (23.7%) vs. 14(5.7%) (RR 3.8(2.1-7) p < 0.0001) but a similar rate of complications compared to HIVi children 34 (41.5%) (RR = 0.6 (0.3-1.1) p = 0.06). Conclusion HIVe children have a higher risk of developing complications and mortality after surgery compared to HIVn children. However, the risk of complications is lower than that of HIVi children.